Relaxed Selection During a Recent Human Expansion. Issue 2 (1st February 2018) - Peischl, Stephan; Dupanloup, Isabelle; Foucal, Adrien; Jomphe, Michèle; Bruat, Vanessa; Grenier, Jean-Christophe; Gouy, Alexandre; Gilbert, K J; Gbeha, Elias; Bosshard, Lars; Hip-Ki, Elodie; Agbessi, Mawussé; et al.
Abstract: Peischl et al . explore the way evolutionary forces shape genetic variability in expanding human populations. Over a few generations of separate evolution... Humans have colonized the planet through a series of range expansions, which deeply impacted genetic diversity in newly settled areas and potentially increased the frequency of deleterious mutations on expanding wave fronts. To test this prediction, we studied the genomic diversity of French Canadians who colonized Quebec in the 17th century. We used historical information and records from ∼4000 ascending genealogies to select individuals whose ancestors lived mostly on the colonizing wave front and individuals whose ancestors remained in the core of the settlement. Comparison of exomic diversity reveals that: (i) both new and low-frequency variants are significantly more deleterious in front than in core individuals, (ii) equally deleterious mutations are at higher frequencies in front individuals, and (iii) front individuals are two times more likely to be homozygous for rare very deleterious mutations present in Europeans. These differences have emerged in the past six to nine generations and cannot be explained by differential inbreeding, but are consistent with relaxed selection mainly due to higher rates of genetic drift on the wave front. Demographic inference and modeling of the evolution of rare variants suggest lower effective size on the front, and lead to an estimation of selection coefficients that increase with conservation scores. Even though range expansions have had a relatively limited impact on the overall fitness of French Canadians, they could explain the higher prevalence of recessive genetic diseases in recently settled regions of Quebec.